Role of post‐translational modifications in the acquisition of drug resistance in Mycobacterium tuberculosis. (23rd October 2020) - Arora, Gunjan; Bothra, Ankur; Prosser, Gareth; Arora, Kriti; Sajid, Andaleeb
Abstract : Tuberculosis (TB) is one of the primary causes of deaths due to infectious diseases. The current TB regimen is long and complex, failing of which leads to relapse and/or the emergence of drug resistance. There is a critical need to understand the mechanisms of resistance development. With increasing drug pressure, Mycobacterium tuberculosis ( Mtb ) activates various pathways to counter drug‐related toxicity. Signaling modules steer the evolution of Mtb to a variant that can survive, persist, adapt, and emerge as a form that is resistant to one or more drugs. Recent studies reveal that about 1/3rd of the annotated Mtb proteome is modified post‐translationally, with a large number of these proteins being essential for mycobacterial survival. Post‐translational modifications (PTMs) such as phosphorylation, acetylation, and pupylation play a salient role in mycobacterial virulence, pathogenesis, and metabolism. The role of many other PTMs is still emerging. Understanding the signaling pathways and PTMs may assist clinical strategies and drug development for Mtb . In this review, we explore the contribution of PTMs to mycobacterial physiology, describe the related cellular processes, and discuss how these processes are linked to drug resistance. A significant number of drug targets, InhA, RpoB, EmbR, and KatG, are modified at multiple residues via PTMs. A better understanding of drug‐resistance regulons and associated PTMs will aid in developing effective drugs against TB. Abstract : Overlap in signaling schemes: Post‐translational modifications regulate proteins located at different sites of the M. tuberculosis genome, although proteins at some loci are modified exclusively. The overlap between PTMs is observed with many proteins that are critical for survival and important drug targets. Genome sequence of M. tuberculosis H37Rv was used to prepare the map by ClicO FS software.